1992
DOI: 10.1111/j.1464-410x.1992.tb15579.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Fibrous Histiocytoma of the Renal Capsule

Abstract: A 49-year-old female discovered a tumour in her abdomen shortly before being admitted to hospital. Her previous history was uneventful.Examination revealed a mobile, large, hard tumour in the right hypogastric region. Haematological and biochemical tests, chest X-ray and bone scan showed no abnormalities. Intravenous urography showed normal structures on the left side but on the right only the upper calices appeared normal. The rest of the renal pelvis was obscured by a 12-cm turnour. Sonography identified a 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…In a review of the international literature based basically on Medline, we revealed reports of only 23 patients with documented diagnosis of primary renal MFH in the period 1974-1997 [7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and to this we add our recent case. The above-mentioned patients ranged in age from 35 to 82 years and mean age of 59 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a review of the international literature based basically on Medline, we revealed reports of only 23 patients with documented diagnosis of primary renal MFH in the period 1974-1997 [7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and to this we add our recent case. The above-mentioned patients ranged in age from 35 to 82 years and mean age of 59 years.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the cases occurs in the trunk, the extremities and the retroperitoneum [1,2]. Primary involvement of the retroperitoneum or kidney is rare and accounts for 12-14% of all MFH cases [7], whilst it composes only 1-3% of malignant renal tumors in general [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13,16,17] Because most renal MFHs arise from the capsule, intracavitary progression and consecutive hematuria are rare. [13,18,19] Symptoms, a physical examination, and imaging are insufficient for differentiating MFH from other renal tumors, and histopathology is essential for its differentiation. [18][19][20][21] MFH is a common type of soft tissue sarcoma that was initially described four decades ago, and it has been shown to have the characteristics of both mesenchymal cells and mononuclear phagocytes [22][23][24] The most common renal sarcomas are characterized by typical immunophenotypes that include negativity for CD68.…”
Section: Discussionmentioning
confidence: 99%
“…The role of adjuvant radiotherapy is questionable and offers little, if any, benefit. [14,18,19,21] Only early radical surgery and postoperative polychemotherapy can achieve success. [13,20] If local infiltration or distant metastases are present, treatment with polychemotherapy may be indicated, although the effectiveness is questionable and the response rate is only 33%.…”
Section: Discussionmentioning
confidence: 99%